2020
DOI: 10.1186/s13643-020-01437-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of freshly cultured versus freshly thawed (cryopreserved) mesenchymal stem cells in preclinical in vivo models of inflammation: a protocol for a preclinical systematic review and meta-analysis

Abstract: Background Mesenchymal stem cells (MSCs) are multipotent cells that demonstrate therapeutic potential for the treatment of acute and chronic inflammatory-mediated conditions. Especially for acute conditions, it is critical to have a readily available freshly thawed (cryopreserved) MSC product for rapid administration. Although controversial, some studies suggest that MSCs may lose their functionality with cryopreservation which in turn could render them non-efficacious. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A vast preclinical dataset, from both in vitro and in vivo animal studies, supports the notion that MSCs are a potent cellular therapeutic agent. Here, we will review the in vitro preclinical data, but reviews of the in vivo preclinical data can be found here (Vu et al, 2014 ; Squillaro et al, 2016 ; Lukomska et al, 2019 ; Dave et al, 2020 ). Why is there such a gap between the expectations set by preclinical data and human MSC trials?…”
Section: Introductionmentioning
confidence: 99%
“…A vast preclinical dataset, from both in vitro and in vivo animal studies, supports the notion that MSCs are a potent cellular therapeutic agent. Here, we will review the in vitro preclinical data, but reviews of the in vivo preclinical data can be found here (Vu et al, 2014 ; Squillaro et al, 2016 ; Lukomska et al, 2019 ; Dave et al, 2020 ). Why is there such a gap between the expectations set by preclinical data and human MSC trials?…”
Section: Introductionmentioning
confidence: 99%